General health survey in patients with small abdominal aortic aneurysm - Arnautovic, A.; Dalyanoglu, H.; Vallejo Castano, L. J.; Garabet, W.; Mulorz, J.; Knapsis, A.; Düsing, S.; Schellinger, I. N.; Schelzig, H.; Raaz, U.; Duran, M.; Wagenhäuser, M. U. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAbdominal aortic aneurysm (AAA) is a dynamic disease characterized by a continuous diameter progression. AAA may therefore be categorized in early-stage disease (small diameter AAA) and late-stage disease (large diameter AAA). To date, there is no effective therapy for patients in early stages, resulting in disease-specific stressors. This study was designed to quantify these stressors using a specifically designed questionnaire.MethodsA self-designed 17-item questionnaire with categorical response options was distributed to patients with small AAA. The aim of the approach was to gain a deeper understanding of patients' quality of life (QoL), psychological state and attitudes towards hypothetical future treatment options.Results122 patients were contacted, 63 of whom consented to participate in the study. The study cohort was predominantly older than 65 years, 84% were male and 56% had been diagnosed with small-size AAA less than 1 year ago. In summary, the AAA diagnosis has a significant impact on all aspects of personal health perception, including physical, social and mental health. The overall QoL was found to be impaired compared to the situation before the AAA diagnosis for most of the respondents, and the current treatment options were considered unsatisfactory. The majority of small AAA patients surveyed would be open to new (invasive) therapies to stop disease progression.ConclusionThe diagnosis of AAA leads to a reduction in QoL, which impairs the physical, social and mental health, particularly affecting mental health. Patients would welcome treatment options in early stages of their disease.